The classification and selection of indoor shade-tolerant plants of indoor chemical pollution. Issue 6 (February 2019) - Lu, Min; Zhang, Lingfang; Li, Donghe; Lu, Jiahuan; Gao, Peng; Liu, Shunteng
Abstract: It has been an urgent issue of finding a reasonable and safety methods to control the indoor benzene pollution form building materials in China. Twenty two common indoor shade-tolerant plants were tested by artificial closed fumigation to investigate their sensitivity on high concentration formaldehyde and benzene. And then sensitivity of each plant was classified according to the degree of symptoms. The results indicate that Impatiens balsamina, Begonia × aelatior and Melissa officinalis are sensitive to indoor formaldehyde and benzene pollution.